PENGARUH MEDIA KARTU TRUTH OR DARE TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (PPKn) - Anggit Paramita Sari; Ali Mashari; Qomario Qomario (AHSANTA JURNAL PENDIDIKAN, 2020)
This study aims to determine whether there is a positive influence from the use of learning media using Truth or Dare card media on the learning outcomes of Civics class V at SD Negeri 2 Labuhan Ratu Bandar Lampung. This research is a quantitative research with a pre-experimental design that uses a one group pre-test post-test design. The population in this study were fifth grade students at SD Negeri 2 Labuhan Ratu Bandar Lampung. Sampling was taken using non-probability sampling technique using purposive sampling. Data collection techniques and data collection instruments used observation, documentation, and tests. The data analysis technique used is the t-test. The results of the study were shown by the results of the t-test (paired sample t test) for the same sample with different treatments (pre-test post-test) of -5.590 with a Sig. (2-tailed) 0.000 < 0.05. This proves that there is an influence from the use of Truth or Dare card media on the learning outcomes of Civics class V at SD Negeri 2 Labuhan Ratu Bandar Lampung.